Effect of altered haemodynamics on the developing mitral valve in chick embryonic heart - Pang, Kar Lai; Parnall, Matthew; Loughna, Siobhan (Elsevier, 2017)
Intracardiac haemodynamics is crucial for normal cardiogenesis, with recent evidence showing valvulogenesis is haemodynamically dependent and inextricably linked with shear stress. Although valve anomalies have been associated with genetic mutations, often the cause is unknown. However, altered haemodynamics have been suggested as a pathogenic contributor to bicuspid aortic valve disease. Conversely, how abnormal haemodynamics impacts mitral valve development is still poorly understood. In order to analyse altered blood flow, the outflow tract of the chick heart was constricted using a ligature to increase cardiac pressure overload. Outflow tract-banding was performed at HH21, with harvesting at crucial valve development stages (HH26, HH29 and HH35). Although normal valve morphology was found in HH26 outflow tract banded hearts, smaller and dysmorphic mitral valve primordia were seen upon altered haemodynamics in histological and stereological analysis at HH29 and HH35. A decrease in apoptosis, and aberrant expression of a shear stress responsive gene and extracellular matrix markers in the endocardial cushions were seen in the chick HH29 outflow tract banded hearts. In addition, dysregulation of extracellular matrix (ECM) proteins fibrillin-2, type III collagen and tenascin were further demonstrated in more mature primordial mitral valve leaflets at HH35, with a concomitant decrease of ECM cross-linking enzyme, transglutaminase-2. These data provide compelling evidence that normal haemodynamics are a prerequisite for normal mitral valve morphogenesis, and abnormal blood flow could be a contributing factor in mitral valve defects, with differentiation as a possible underlying mechanism.